Mechanism and control of roof fall and support failure incidents occuring near longwall recovery roadways - Zhu, W.; Xu, J.; Xu, Guang (Southern African Institute of Mining and Metallurgy, 2017)
Pre-driven longwall recovery roadways are commonly adopted for rapid extraction in the high-production mines of Shendong coalfield in China. A special roadway, the adapting roadway, is utilized to adapt the longwall roof and floor to match the recovery roadway. However, severe accidents such as roof falls and support failures frequently occurred where this recovery roadways layout was applied to relatively deep coal seams. This posed a serious threat to safe production, and effective recovery and relocation of the longwalls. By analysing different cases and mining conditions, theoretical investigation and numerical simulation were conducted based on the mechanisms of such incidents, and a systematic control approach was proposed. The controls involve a method to determine the applicability of the adapting roadway, the evaluation of incident potential, the means to reduce the likelihood of incidents, and an optimized method to determine the location of mesh installation. The findings were applied to multiple longwall faces in the Shendong coalfield and resulted in substantial benefits. The study findings and the proposed control approach can also be applied to other mines with similar problems.